Outcomes After Curative Thoracic Radiotherapy in Patients With Coronary Artery Disease and Existing Cardiac Stents. (December 2016) - Sio, Terence T.; Liang, Jackson J.; Chang, Kenneth; Novotny, Paul J.; Prasad, Abhiram; Miller, Robert C.
Abstract : Objectives: To evaluate outcomes among cancer patients with preexisting coronary artery disease and cardiac stenting who subsequently underwent thoracic radiotherapy (RT). Methods: From 1998 to 2012, 147 patients received percutaneous coronary intervention (PCI) and then curative external beam RT (>30 Gy, except for Hodgkin lymphoma patients) involving the heart and the lungs. Heart-specific and lung-specific dosimetric parameters were correlated to overall survival (OS) and cardiac-specific survival by Cox variate methods. Results: The mean interval between PCI and cancer diagnosis was 1.8 years (range, 0.1 to 14.2 y). Hypertension was present in 105 patients (71%), and hyperlipidemia in 82 (56%). At the time of analysis, 69 patients (47%) were alive, 3 (2%) died of cardiac causes, and 53 (36%) died of cancer. In multivariate analyses, OS since PCI was related to cancer type ( P =0.004). Decreased OS since cancer diagnosis was related to older age ( P <0.001) and increased percentage of targeted volume or organ receiving 20 Gy or more for lung ( P <0.001), even after controlling for sex, cancer type, and stage. However, for non–cancer-specific survival and major adverse cardiac event-free survival, older age and underlying cardiopulmonary comorbidities dominated (rather than heart and lung dosimetric parameters) in predicting worse outcome for these patients with preexisting coronary artery disease who later underwent RT. Conclusions: Cancer type, older age, and preexisting cardiopulmonary comorbidities and risk factors most significantly predicted clinical outcome and survival for these patients with existing coronary stents who subsequently received thoracic RT. Dosimetric detrimental effects were not significant in our study. Abstract : Supplemental Digital Content is available in the text.